Restoring Genital Hiatus to Normative Values After Apical Suspension Alone Versus With Level 3 Support Procedures. Issue 3 (May 2019) - Carter-Brooks, Charelle M.; Lowder, Jerry L.; Du, Angela L.; Lavelle, Erin S.; Giugale, Lauren E.; Shepherd, Jonathan P.
Abstract : Objective: The aim of the study was to evaluate postoperative genital hiatus after apical suspension procedures without a level 3 support procedure (L3SP), posterior repair, and perineorrhaphy, compared with normative-value genital hiatus of 3.4 cm. Methods: This an analysis of a pre-existing retrospectively collected database that included all minimally invasive sacrocolpopexies and uterosacral ligament suspensions performed at a tertiary medical center from January 2009 to August 2015. Results: We identified 1006 surgical cases: 160 (15.9%) apical suspensions with L3SPs and 846 (84.1%) without. Mean (SD) age was 59 (9) years and body mass index was 27.6 (4.7) kg/m 2 . Women were mainly white (97.4%) with stage III prolapse (67.8%). Those who underwent L3SPs were more likely to be premenopausal and undergo hysterectomy and USLS. Baseline genital hiatus was similar with and without L3SPs (4.8 [1.2] cm vs 4.6 [1.1] cm, P = 0.096). Postoperative genital hiatus was reduced beyond normative (3.4 cm) after apical suspension without (3.0 [0.7] cm, P < 0.001) and with (2.8 [0.9] cm, P < 0.001) L3SPs. Postoperative genital hiatus after L3SPs was similar to those without (2.8 [0.9] cm vs 3.0 [0.7] cm, P = 0.06). We found that change in genital hiatus was greater, by 0.7 cm, when L3SP was performed versus not performed (2.3 [1.2] cm vs 1.6 [1.1] cm, P < 0.001). Conclusions: Level 3 support procedures may be unnecessary to restore genital hiatus to normal at time of apical suspension procedures and should be reserved for select patients. Abstract : Level 3 support procedures may be unnecessary to restore genital hiatus to normal at time of apical suspension procedures.